2017
DOI: 10.3390/cryst7030085
|View full text |Cite
|
Sign up to set email alerts
|

The Syntheses, Crystal Structure and Luminescence Properties of Cone-Like Octadentate Europium (III) Complexes with Four Short Alkoxy Substituents

Abstract: Treatment of 1-(4 -methoxy or ethoxy phenyl)-4,4,4-trifluoro-1,3-butanedione with europium (III) chloride in the presence of piperidine resulted in the halide ligands exchange yielded new piperidinium tetrakis{1-(4 -methoxy or ethoxy phenyl)-4,4,4-trifluoro-1,3-butanedionato} europate (III) complexes 2a and 2b. Complexes 2a and 2b have been characterized by elemental analysis, 1 H NMR spectroscopy, and FAB-MS, and their absolute structures were determined by single crystal X-ray diffraction analysis. The compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Therefore, the excited energy on the f orbital ( 5 D levels) of the centered europium ion is effectively relaxed to 7 F levels only. Our recent research reported that the octa-coordinate homoleptic and heteroleptic europate (III) complexes carrying four bidentate ligands were synthesized and the structure of the homoleptic complex was unexpectedly cone-like by X-ray analysis without water molecule(s) as the ligand(s) [13]. The luminescent intensity of the complex was quite strong because the complex has no water ligand in solid and in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the excited energy on the f orbital ( 5 D levels) of the centered europium ion is effectively relaxed to 7 F levels only. Our recent research reported that the octa-coordinate homoleptic and heteroleptic europate (III) complexes carrying four bidentate ligands were synthesized and the structure of the homoleptic complex was unexpectedly cone-like by X-ray analysis without water molecule(s) as the ligand(s) [13]. The luminescent intensity of the complex was quite strong because the complex has no water ligand in solid and in solution.…”
Section: Introductionmentioning
confidence: 99%